From the bench to exploration medicine: NASA life sciences translational research for human exploration and habitation missions - Joshua S. Alwood (Nature Portfolio, 2017)
Abstract NASA’s Space Biology and Human Research Program entities have recently spearheaded communications both internally and externally to coordinate the agency’s translational research efforts. In this paper, we strongly advocate for translational research at NASA, provide recent examples of NASA sponsored early-stage translational research, and discuss options for a path forward. Our overall objective is to help in stimulating a collaborative research across multiple disciplines and entities that, working together, will more effectively and more rapidly achieve NASA’s goals for human spaceflight.